A Scientometric Analysis of Green Innovation and Business Models - Judijanto, Loso; Iswanto, Juni (Westscience Press, 2025)
This study conducts a large-scale scientometric analysis of green business models and green innovation literature to map the intellectual structure, thematic evolution, and global collaboration patterns of this multidisciplinary science. Based on data drawn from the Scopus database from 2000–2025, the study employs VOSviewer software to perform co-authorship, co-citation, and keyword co-occurrence analysis. The results highlight four dominant thematic clusters centered around green innovation, circular economy, digital transformation, and green economy, revealing how these concepts have evolved and intersected over time. China, the United Kingdom, and India emerge as leading contributors, while institutions such as Jiangsu University and Xi’an Jiaotong University play pivotal roles in global research collaboration. The overlay and density visualizations show a surge of interest in digitalization, artificial intelligence, and ESG integration in recent years. The paper provides theoretical and empirical insights for researchers, policymakers, and practitioners aiming to understand and leverage the evolving forces behind sustainable business model innovation in the green transition era.